Validation and extension of a simple questionnaire to assess physical activity in pre-school children - Bayer, Otmar; Jarczok, Marc N.; Fischer, Joachim E.; Bock, Freia de (Public health nutrition, 2012)
Objective: To (i) validate a recently proposed questionnaire tool for the simple assessment of physical activity (PA) in pre-school children by comparison with accelerometry and heart-rate recordings; and (ii) extend the tool by adding more questions to improve validity and to refine the classification from two to three categories (PA low, medium, high).Setting: Baseline data of an intervention evaluation study.Subjects: Pre-school children.DesignChildren were categorized as either physically active or non-active, based on their parents’ answers to the five-item questionnaire. Activity and heart rate were recorded for 6 d (Actiheart device; CamNtech, Cambridge, UK). Nightly sleeping periods were removed and mean accelerometry counts (MACT), time spent in moderate-to-vigorous intensity physical activity (MVPA) and time spent in sedentary behaviour (SB) were computed. In a second step, additional questions that improved validity were added, resulting in an extended seven-item questionnaire.Results: For 748 (90·4 %) of the participating children aged 2·3-6·7 years, the questionnaires were filled out sufficiently for classification. Children classified as physically active showed 9·6 % higher MACT (P < 0·0003), spent more time in MVPA and insignificantly less time in SB. Using the extended questionnaire, children with PA classified as medium (reference: low) showed 11·0 % more MACT, spent 11·8 % more time in MVPA and 4·8 % less time in SB. Children with PA classified as high showed 16·9 % more MACT, spent 20·2 % more time in MVPA and 7·2 % less time in SB.Conclusions: With validated PA questionnaires for pre-school children lacking, the proposed questionnaire might be a reasonable option to include for PA assessment in epidemiological studies where more elaborate measurements are unavailable.